Technology Adoption Among Women in Cambodia's SMEs: Influencing Factors, Benefits, and Coping Strategies - Dathalineth Mam; Narith Por; Bunly Kep (MASI Mandiri Edukasi, 2025)
Technology adoption is crucial for enhancing efficiency and competitiveness, especially for women in Cambodia's small and medium-sized enterprises (SMEs). Despite SMEs being recognized as key drivers of economic growth, women entrepreneurs face significant challenges, including limited digital awareness, weak technology support, and restricted access to resources. This study explores the factors influencing technology adoption, benefits, and coping strategies. Data were collected from 121 women entrepreneurs in Cambodia's SMEs using a self-administered survey. Descriptive and inferential statistical analyses, including correlation analysis, were employed to assess the relationships between adoption factors, benefits, and coping strategies. The study identified six key factors influencing technology adoption: operational optimization, client and business relationships, market expansion, information accessibility, cost considerations, and adoption. It also found four key benefits of technology adoption: improved information management, enhanced communication, increased operational efficiency, and a strengthened business reputation. Common strategies to overcome adoption barriers included human-centred approaches, such as workforce training and leadership engagement, and operational strategies, like reducing internet costs and improving connectivity. Results showed a strong positive relationship between adoption factors and perceived benefits (r = 0.7779, p < 0.0001) and a moderate correlation with coping strategies (r = 0.5642, p < 0.0001), confirming that as adoption factors improve, the benefits and coping strategies also strengthen. This study fills a critical research gap by focusing on the underexplored experiences, providing actionable insights for policymakers and business leaders. It emphasizes the need for policy support, infrastructure improvements, and training programs to foster a technology-driven business environment.